Air Traffic Controller Stress and Stress Management in Antigua, Barbados and Guyana - Scotland, Brent (2017)
A review of the literature on stress and air traffic control reveals that air traffic control is a stressful profession. However, no statistical information of the percentages of stressed or unstressed air traffic controllers (with which to compare to the results of this study) were found during the literature review. Statistics provided by the airport authorities of each relevant country showed average traffic levels annually for the previous 4 years: 52816 flights for Antigua (high); 36324 for Barbados (medium); and 30382 for Guyana (low).